Las artes plásticas como técnica de la educación para fortalecer el desarrollo de la psicomotricidad fina de los niños y niñas del tercer año de Educación Básica de la escuela Federación Deportiva de Cotopaxi período lectivo 2016-2017. - Muñoz Cajas, Pamela Geovannna (2017)
The arts project is presented in order to help stimulate the development of skills and abilities in basic education, through the implementation of techniques and methodologies for the improvement of motor areas. Research started from a general diagnosis of the level psychomotor of the boys and girls of the school of basic education "Federación Deportiva de Cotopaxi", La Maná town, which began recognizing the environment in which they operate. The school has 200 students 120 and 80 children, which are distributed by an average of 30 years by respective parallel. The research relies on the application of several methods such as descriptive, analytical, synthetic and observation, supported by techniques such as surveys and interviews; the theoretical foundation was structured with the conceptualization of different components bibliographic as art, origin of art, visual arts, its importance and impact in education, technical graph - plastic, in addition to the observation, manipulation of each of the topics and subtopics the development of psychomotor skills-oriented fine for the integral formation of the learner. By it exposed is proposes the elaboration of a guide pedagogical for the management and application of technical of plastic arts, that facilitate the educational work in teaching.